Acute, periprocedural and longterm antithrombotic therapy in older adults - Andreotti, Felicita (2023)
The first international guidance on antithrombotic therapy in the elderly came from the European Society of Cardiology Working Group on Thrombosis in 2015. This same group has updated its previous report on antiplatelet and anticoagulant drugs for older patients with acute or chronic coronary syndromes, atrial fibrillation, or undergoing surgery or procedures typical of the elderly (transcatheter aortic valve implantation and left atrial appendage closure). The aim is to provide a succinct but comprehensive tool for readers to understand the bases of antithrombotic therapy in older patients, despite the complexities of comorbidities, comedications and uncertain ischaemic- vs. bleeding-risk balance. Fourteen updated consensus statements integrate recent trial data and other evidence, with a focus on high bleeding risk. Guideline recommendations, when present, are highlighted, as well as gaps in evidence. Key consensus points include efforts to improve medical adherence through deprescribing and polypill use; adoption of universal risk definitions for bleeding, myocardial infarction, stroke and cause-specific death; multiple bleeding-avoidance strategies, ranging from gastroprotection with aspirin use to selection of antithrombotic-drug composition, dosing and duration tailored to multiple variables (setting, history, overall risk, age, weight, renal function, comedications, procedures) that need special consideration when managing older adults. © The Author(s) 2022. Published by Oxford University Press on behalf of European Society of Cardiology. All rights reserved.